Association of coronary lipid core plaque with intrastent thrombus formation. Issue 3 (10th January 2012) - Papayannis, Aristotelis C.; Abdel‐Karim, Abdul‐Rahman R.; Mahmood, Arif; Rangan, Bavana V.; Makke, Lorenza B.; Banerjee, Subhash; Brilakis, Emmanouil S.
<x xml:space="preserve">Abstract</x> Background: Optical coherence tomography (OCT) and near‐infrared spectroscopy (NIRS) allow assessment of the anatomy (OCT) and composition (NIRS) of coronary lesions. We sought to examine the association between pre‐stenting lipid core plaque (LCP), as assessed by NIRS and post‐stenting thrombus formation, as assessed by OCT. Methods: We reviewed the angiograms of nine patients who underwent coronary stenting in association with NIRS and OCT imaging. A large LCP by NIRS was defined as at least three 2‐mm yellow blocks on the NIRS block chemogram with >200° angular extent. Intracoronary thrombus was defined as a mass of medium reflectivity protruding into the vessel lumen, discontinuous from the surface of the vessel wall. Results: Mean age was 67 ± 7 years, and all patients were men, presenting with stable angina (56%), unstable angina (11%), or acute myocardial infarction (33%). The mean vessel lipid core burden index (LCBI) was 120 ± 45, and the mean highest 6‐mm LCBI was 386 ± 190. Three patients had a large LCP and two of them (66%) developed intrastent thrombus after stent implantation compared to none of six patients without large LCPs (0%, P = 0.02). The thrombus resolved after intracoronary glycoprotein IIb/IIIa administration and balloon postdilation. Postprocedural myocardial infarction occurred in 33% versus 17% of patients with and without large LCP, respectively (P = 0.57). Conclusion: Stenting of large LCPs may be associated with intrastent thrombus formation, suggesting that more intensive anticoagulant and/or antiplatelet therapy may be beneficial in such lesions. © 2012 Wiley Periodicals, Inc.